Indications for psychiatric safety measures : a retrospective study - Buzina, Nadica (Array, 2009)
Abstract: The aim of this article has been designed to investigate the influence of particular diagnostic categories on recommendations for safety measures, and to investigate the impact of constellatory factors, as the states of acute alcoholism, acute intoxication by psychoactive drugs and intense affect, on the recommendations for safety measures. The sample consisted of 120 examinees forensically expertised at the Center for Forensic Psychiatry of the Psychiatric Hospital Vrap~e in the period from January 1, 1998 to December 31, 1999, and evaluated as less responsible according to the new Penal Code. All the examinees had the same legal presumptions for safety measures (decreased responsibility). The sample was divided into two groups: a group of examinees for whom a safety measure had been recommended and a group without such recommendations. The basic methodological instrument was a specially designed questionnaire with 137 items. Regarding socio-demographic characteristics, no statistically significant differences existed between the two groups taking into account age, gender, level of education and marstatus. The diagnosis of personality disorder, as the first one, did not influence recommendations for safety measures. Alcohol and drug abuse were statistically significantly present in the group with recommended measures as second diagnoses, and besides influencing responsibility, had an impact on the recommendation of safety measures. An intense affect influenced the reduction of responsibility, but not the suggestion of safety measure, while alcohol and drug intoxications, besides affecting responsibility, had an impact on the suggestion of safety measure. The decisive impact of dependence influenced the recommendation for safety measures